1978
DOI: 10.3382/ps.0570022
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Force Molting on the Incidence of Uncollectable Eggs

Abstract: Two experiments were conducted to determine the influence of force molting on egg shell quality. Approximately 15,000 Honegger and 15,000 Babcock hens, 17 months of age, were force molted using conventional methods. Just prior to force molting, the incidence of shell-less, ultra-thin shell and thin-shell eggs (uncollectable) was determined. Sheets of metal were hung at random beneath the cages of 800 birds in each population to catch all eggs that dropped through the cages. Fifty hard-shell eggs were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Results suggest that most of the improvement in production by molting was not caused by an increase in ovulation rate but by a decrease in SL egg production. This confirmed the previous data of Roland and Bushong (1978). ProduxtiojLofJiens laying at the lowest rate was improved the most because they were probably laying the most SI.…”
Section: Resultssupporting
confidence: 93%
“…Results suggest that most of the improvement in production by molting was not caused by an increase in ovulation rate but by a decrease in SL egg production. This confirmed the previous data of Roland and Bushong (1978). ProduxtiojLofJiens laying at the lowest rate was improved the most because they were probably laying the most SI.…”
Section: Resultssupporting
confidence: 93%
“…In contrast, those hens of the HS egg layer group had a total average hen-day production of 60.0% with only 3.2% of the total representing SS and SL eggs. The production of SS eggs was reduced following an induced molt, which agrees with observations of Roland and Bushong (1978).…”
Section: Egg Productionsupporting
confidence: 89%
“…3 Present address: Governors State University, Division of Science, University Park, IL 60466. SS and SL egg production for at least 13 weeks postmolt (Roland and Bushong, 1978). Improved postmolt performance is due primarily to a reduction in SL egg production rather than an increase in ovulation (Roland and Brake, 1982).…”
Section: Introductionmentioning
confidence: 98%
“…Noles (1966) and Nakazawa et al (1970) also reported that egg weight was unaffected by molt. Roland and Bushong (1978) stated that force molting generally had little influence on egg weight. Improved shell quality, as well as albumen quality, during the 20-week postmolt period was reported by Hembree et al (1980).…”
Section: Resultsmentioning
confidence: 98%